Análise da relação causal entre imagem de destinos, qualidade, satisfação e fidelidade: um estudo de acordo com a percepção do turista nacional no destino turístico Natal - Chagas, Márcio Marreiro das (2010)
This dissertation aims to analyze the causal relationship between the quality of tourist services, satisfaction with the attributes and globally, fidelity and image of tourist destinations. Therefore, it was conducted an exploratory, descriptive research with quantitative analytical approach. Data collection was performed by a questionnaire addressed to tourists at the Augusto Severo International Airport and Bus station of Natal, the main points of entry and exit of tourists. The composition was simple random sampling by reaching the final number of 400 tourists interviewed. Among the main results, is an assessment of the quality of the components of the destination. It was noted that nine are the dimensions of perceived quality of tourism products and services of ―Sun and Sand‖ segment, that is, Beaches and Facilities, Public Equipment, Catering Services, Transportation, Hotel Equipment, Hotel Services, Entertainment & Attractions, Access to the Hotel and Hospitality. Moreover, it was concluded that the Preview Tourism Destination Image has little direct influence in the Consumer Satisfaction, and only indirectly in the Post-Purchase Behavior. While the Complex Tourism Destination Image exerts strong and direct influence on both factors, in the Customer Satisfaction Process and Loyalty, the dimensions of quality also claimed to be strongly influences both factors